The transformation of knowledge production in industrial technology R&D institutes in Vietnam - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
In the process of economic transition from a centrally planned economy to a market oriented one, science and technology (S&T) institutions in general and industrial technology R&D institutes in particular in Vietnam have also undergone their institutional transformation to response to the changing conditions created by the market. It was believed that a technology market can play a mediating role between the R&D institutions and enterprises and commercialization of technology is a solution to the poor exploitation of knowledge in Vietnam’s S&T system. The paper attempts to question the underlying assumption of the role of the technology market and policy initiatives supporting the commercialization of technology from institutionalize approach. It examines the interconnection between the transition of S&T policy (from policy for science to science in policy, policy for technological innovation, and recently to policy for distributed knowledge production) and the transformation of knowledge production in Vietnam. Using the two case studies on industrial technology R&D institute, the paper aims at illustrating the changing way of producing and exploring scientific and technological knowledge in R&D institutions and identifying institutional changes that facilitate the transformation of knowledge production towards socially distributed knowledge production. Code: 16111801